2022
DOI: 10.1161/strokeaha.122.040330
|View full text |Cite
|
Sign up to set email alerts
|

Depression or Anxiety According to Management Modalities in Patients With Unruptured Intracranial Aneurysms

Abstract: BACKGROUND: In the treatment of unruptured intracranial aneurysms, the risk was usually estimated by objective neurological sequelae. However, their effects on depression and anxiety are rare and remain controversial. We aimed to evaluate the risk of depression and anxiety in patients with unruptured intracranial aneurysm stratified by management strategies in a population-based, longitudinal cohort study. METHODS: Using the Korean National Health Insur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It was postulated that the impacts of stroke on QOL might be mediated through these health problems. Functional disability was identified as a predictor for poor QOL among stroke patients in China [56], UK [58], and US [59], while the risk of depression was higher, especially among stroke patients in older age groups [60]. The study from China also found that stroke patients with a low income level had a poorer HRQoL [56].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It was postulated that the impacts of stroke on QOL might be mediated through these health problems. Functional disability was identified as a predictor for poor QOL among stroke patients in China [56], UK [58], and US [59], while the risk of depression was higher, especially among stroke patients in older age groups [60]. The study from China also found that stroke patients with a low income level had a poorer HRQoL [56].…”
Section: Discussionmentioning
confidence: 94%
“…Stroke is a major health problem with a significant impact on the QOL. Studies have shown that stroke patients are more likely to report a poorer QOL and health problems, such as disability or poor functional status [55][56][57][58][59] and anxiety or depression [60,61]. It was postulated that the impacts of stroke on QOL might be mediated through these health problems.…”
Section: Discussionmentioning
confidence: 99%
“…We identified patients newly diagnosed with MMD from January 1, 2008, to December 31, 2020, and we followed them up to December 31, 2021. A 1-year washout period (2007-2008) was used to prevent prevalent cases from interfering with the data for inclusion, exclusion, and confounding factors . We improved the accuracy of patient identification by using specific operational definitions.…”
Section: Methodsmentioning
confidence: 99%
“…A 1-year washout period (2007)(2008) was used to prevent prevalent cases from interfering with the data for inclusion, exclusion, and confounding factors. 11,12 We improved the accuracy of patient identification by using specific operational definitions. The diagnosis of MMD was established if International Statistical Classification of Diseases, Tenth Revision (ICD-10), code I67.5 and RID code V128 were newly recorded at least once in the database at hospital discharge or more than twice in the outpatient department.…”
Section: Study Participants Comorbidity and Outcome Variablesmentioning
confidence: 99%